Flower girl - Perry, Chrissie; Fukuoka, Aki (Hardie Grant Egmont Richmond, Vic., 2011)
Lola's mum and step-dad are getting married, and Lola is going to be flower girl! But there's another flower girl as well--will she drive Lola crazy?